IMPLEMENTATION OF A CULTURE-BASED LEARNING MODEL INTEGRATING BUGIS-MAKASSAR PHILOSOPHY IN BASIC MATHEMATICS: A QUALITATIVE EXPLORATION - Ma’rup Ma’rup; Nurdin Arsyad; Abdul Rahman (MATEMATIKA DAN PEMBELAJARAN, 2026)
Mathematics education in elementary schools frequently encounters a dichotomy with students' cultural realities, rendering abstract concepts difficult to internalize. This study explores and describes the implementation of a mathematics learning innovation based on the Bugis-Makassar Philosophy (BBM model) to create a synergy between numerical concepts and indigenous culture. Utilizing a descriptive-exploratory qualitative approach, the research involved 28 fifth-grade students at Elementary School 141 Pakka, Sinjai Regency, focusing on the geometry of cube and cuboid nets. Data was triangulated through systematic observation, semi-structured interviews, learning achievement tests, sociometric questionnaires, and student response surveys. The novelty of this research lies in the systematic integration of four philosophical pillars—Siri’, Pacce’, Abbulosibatang, and Sipakatau—as an active pedagogical framework, transcending the use of ethnomathematics as a mere instructional object. The findings reveal that: (1) The BBM Model transforms the instructional process into a space for character building and ethical development; (2) Empirically, conceptual understanding improved significantly, with average scores rising from 23.75 to 59.11; (3) The dynamics of Pacce’-based peer tutoring and Abbulosibatang-based collaboration effectively mitigated cognitive learning barriers; and (4) The innovation garnered an absolute positive response (100%) from participants. This study concludes that the BBM model serves not only as a cognitive scaffold but also as a paradigm for revitalizing cultural identity, functioning as an ethical foundation for achieving numeracy excellence. These findings provide a substantial theoretical contribution to the formulation of local wisdom-based curricula that can reconcile formal education with students' sociocultural values.   Keywords: Mathematics Education; Ethno-pedagogy; Bugis-Makassar Philosophy; BBM Learning Model; Character-based Learning